eCM 2018
DOI: 10.22203/ecm.v035a23
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a complex bone tissue model with endothelialised channels and capillary-like networks

Abstract: In engineering of tissue analogues, upscaling to clinically-relevant sized constructs remains a significant challenge. The successful integration of a vascular network throughout the engineered tissue is anticipated to overcome the lack of nutrient and oxygen supply to residing cells. This work aimed at developing a multiscale bone-tissue-specific vascularisation strategy. Engineering pre-vascularised bone leads to biological and fabrication dilemmas. To fabricate channels endowed with an endothelium and suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Gelatine is a commonly used ECM component in cell culture and its derivative GelMA is well characterized and widely used in 3D bioprinting, which Yue et al reviewed comprehensively 36 . Many cell types of different tissue origin have been cultured successfully on GelMA: endothelial (HUVEC 37,38 , ECFC 39 ) and epithelial cells (Ishikawa 40 , BeWo 41 ) as well as cells of mesenchymal origin (NIH-3T3 42 , MG63, osteoblasts 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gelatine is a commonly used ECM component in cell culture and its derivative GelMA is well characterized and widely used in 3D bioprinting, which Yue et al reviewed comprehensively 36 . Many cell types of different tissue origin have been cultured successfully on GelMA: endothelial (HUVEC 37,38 , ECFC 39 ) and epithelial cells (Ishikawa 40 , BeWo 41 ) as well as cells of mesenchymal origin (NIH-3T3 42 , MG63, osteoblasts 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the significant modification of physical properties allowed printing of complex structures, whether the increased stiffness influenced stem cell differentiation and tissue formation was not examined. It has been shown that the osteogenic differentiation of HBMSCs within 3D matrices occurs preferentially in substrates from 10 to 30 kPa [47], while vascularisation of tissue engineered constructs is favoured in softer matrices below 5 kPa [48]. Furthermore, culture media and additional cell-signaling cues can produce a synergistic effect on cell function and differentiation [48,49].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been shown that the osteogenic differentiation of HBMSCs within 3D matrices occurs preferentially in substrates from 10 to 30 kPa [47], while vascularisation of tissue engineered constructs is favoured in softer matrices below 5 kPa [48]. Furthermore, culture media and additional cell-signaling cues can produce a synergistic effect on cell function and differentiation [48,49]. In the bioink system reported herein, the addition of LPN resulted in unchanged mechanical strength of GelMA (8 kPa) while maintaining significantly enhanced printability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[ 271 ] Additionally, incorporation of tubular networks in bioprinted tissues is highly relevant for a wide array of applications, as many tissues present microtubular structures (kidney, bile ducts, milk ducts, among others). Commonly used bioinks, including gelatin-, collagen- and fibrin-derived, have been optimized to support both vascular cells and tissue-specific cells, [ 272 , 273 ] taking advantage of the spontaneous ability of endothelial cells to reorganize themselves into capillary networks, when embedded in soft, cell adhesive hydrogels. Aiming for vascularized bone engineering a vasculogenesis-supportive bioink, based on gelatin/alginate blends and HUVECs was reinforced via coprinting with a PCL-based reinforcing frame.…”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%